AID-PRIGSHARE: Automatization of indicator development in green space health research in QGIS. Accompanying script to the PRIGSHARE reporting guidelines - Cardinali, Marcel; Beenackers, Mariëlle A.; van Timmeren, Arjan; Pottgiesser, Uta (Software Impacts)
In the interdisciplinary field of green space health research, there is a demand to reduce the effort to assess green space, especially for non-spatial disciplines. To address this issue, we developed AID-PRIGSHARE, an open-source script that automates over 400 QGIS processes to substantially reduces the time-intensive task of generating green space indicators. AID-PRIGSHARE calculatesgreenness, green space amount, access to green infrastructure, and green space uses within distances of 100–1500 m around geolocations. This substantially reduces the effort for sensitivity analysis and may provide support for research that aims to understand the impact of green space indicators on health outcomes.
Keywords: Green space; Sensitivity analysis; Indicator; GIS; Script; Automatization